KORELASI LAMA MENJALANI HEMODIALISIS DENGAN INDEKS MASSA TUBUH PASIEN GAGAL GINJAL KRONIK DI RSUD ARIFIN ACHAMAD PROVINSI RIAU PADA BULAN MEI TAHUN 2014 - Ratika Widyastuti; WR. Butar-Butar; Eka Bebasari (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Renal failure is a disesase causes a progresive and irreversible reduction of kidney’s function to filtrate waste products from the blood. Indonesia’s prevalence of chronic renal failure is about 0.2 %. Patient with chronic renal failure will achieved severe damage on kidney which will leads to emergency. This research was analytic study with consecutive sampling method to determined the correlation between hemodialysis duration with body mass index on chronic renal failure patients in General Hospital Arifin Achmad Riau Province on May 2014. Sample was taken by measuring patients’ weight and height in Hemodialysis Unit General Hospital Arifin Achmad Riau Province on 2014, where have obtained as many as 58 people. The result showed that chronic renal failure patients most have underwent hemodialysis at age group 45-65 years old (72.4 %), commonest in women about 51.7 %, most hemodialisys frequency was twice a week for four hours(51.7 %). Most of patients had undergone hemodialisys duration about > 12 months (53.4 %). This research was processed by using statistic test correlation Lambda, results have shown a significant and moderate correlation between duration of hemodyalisis and body mass index (r=0.40;p<0,001), which was led to a conclusion: hemodyalisis duration will effect patients’ body mass index.Keywords: Renal failure, hemodialysis, body mass index.